PENGUATAN ECOLOGICAL CITIZENSHIP SEBAGAI UPAYA MENGUBAH PERILAKU MASYARAKAT SADAR AKAN LINGKUNGAN MELALUI PROGRAM KAMPUNG SELO BERAKSI - Hesti Fatmalasari; Erna Yuliandari; Dewi Gunawati (PKn Progresif : Jurnal Pemikiran dan Penelitian Kewarganegaraan, 2019)
This study aims to find out: (1) Strengthening ecological citizenship in changing the behavior of people aware of the environment through the Kampung Selo Beraksi program; (2) Obstacles faced in realizing the Kampung Selo Beraksi program. This study uses qualitative research methods and descriptive research approaches. The research technique used was purposive sampling. Data collection uses interviews, observation and document analysis. Testing data validity using data triangulation and methods. Data analysis uses an interactive analysis model which includes: data reduction, data presentation, and conclusion drawing. Stages of research include: (1) Preparation; (2) Data collection; (3) Analysis of data; (4) Preparation of research reports. The results of this study include: (1) Strengthening ecological citizenship is needed to arouse community awareness through environmental activities, namely the Kampung Selo Beraksi program. Insightful activities in the Kampung Selo Beraksi program include garbage banks, hydroponic parks, vertical gardens, craft galleries, and outbound. Strengthening ecological citizenship in the Kampung Selo Beraksi program is a bottom up approach that is realized through the formation of environmental knowledge, environmental skills, environmental attitudes, environmental participation. (2) The obstacles faced in realizing the Kampung Selo Beraksi program come from internal and external. The barriers to the Kampung Selo Beraksi program originating from the internal include: a) limited human resources due to lack of activeness and participation of the Kampung Selo community members; b) limited sources of funds in the development of the Kampung Selo Beraksi program. Barriers to the Kampung Selo Beraksi program originating from the external include: a) obstacles from the community, namely the existence of counter-attitudes from the community and a lack of community participation; b) obstacles from the government, namely lack of attention and participation of the local government; c) obstacles from the environment, namely the location of Kampung Selo Beraksi far from the city and the maximum arrangement of the village. Keywords: Strengthening, ecological citizenship, Kampung Selo